Role of physical activity and sport in oncology. Issue 1 (April 2015) - Bouillet, T.; Bigard, X.; Brami, C.; Chouahnia, K.; Copel, L.; Dauchy, S.; Delcambre, C.; Descotes, J.M.; Joly, F.; Lepeu, G.; Marre, A.; Scotte, F.; et al.
Highlights PAS in oncology now represents a crucial part of supportive care, with positive effects on resistance to fatigue, cardio respiratory fitness, muscle strength, physical well-being, reduced anxiety and depression, and improved quality of life in the widest sense. This leads to established indications of PAS during and after cancer. The usefulness of a PAS programme intense enough to reach and go beyond intensity, frequency and duration thresholds necessary to obtain a significant benefit. Because of the dose–response relation between physical activity and survival or physiological, psychological and biological effects, cancer survivors who wish to further improve their health may benefit by exceeding the minimum recommended amounts of physical activity and sports. However, this implies a precise definition of the context of clinical management of these patients by means of a genuine prescription of a given type of PAS to a given patient with a given clinical status. In this process, qualified professionals specialised in PAS in oncology are needed to put the prescription into practice. These points are discussed for clinical applications.